2011
DOI: 10.3109/00207454.2011.553753
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Pathology and Spinal Loss in the Visual Cortex in Alzheimer's Disease: A Golgi Study in Pathology

Abstract: Alzheimer's disease is a neurodegenerative disorder characterized by progressive decline in memory, loss of professional skills, impairment of judgement and behavior, and decline in social performances. In terms of neuropathology, the morphological hallmarks of the disease are the accumulation of alpha-beta peptide and the neurofibrillary degeneration, associated with synaptic alterations, involving mostly the dendritic spines. This study is based on the morphological analysis of 10 brains, 5 of which were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 14 publications
2
36
0
5
Order By: Relevance
“…In previous studies of ours using the Golgi method and 3D neuronal reconstruction techniques, severe dendritic and spinal alterations were seen in Alzheimer's disease and normal aged brains [18][19][20].…”
Section: Communicating Authormentioning
confidence: 66%
See 2 more Smart Citations
“…In previous studies of ours using the Golgi method and 3D neuronal reconstruction techniques, severe dendritic and spinal alterations were seen in Alzheimer's disease and normal aged brains [18][19][20].…”
Section: Communicating Authormentioning
confidence: 66%
“…The EW nucleus was identified according to Scinto et al's studies [28,29]. The tissue blocks were coded in order to prevent experimental bias and were used for silver techniques [18][19][20], Congo red method [2], Bielschowsky staining [16], Gallyas technique [33] and Nissl staining [24].…”
Section: Tissue Selection and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies we have shown significant dendritic and spinal changes in the visual cortex during normal ageing [33] and in Alzheimer's disease [32]. In the present study we attempted to describe the morphological and morphometric alterations of the dendrites and the dendritic spines of the pyra midal cells of the visual cortex during normal aging, in order to approach the visual impairment of aged individuals from a neuropathological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we demonstrated significant changes in the pyramidal and stellate cells of the human visual cortex in Alzheimer's disease [30].…”
Section: Introductionmentioning
confidence: 99%